2022
DOI: 10.1097/ta.0000000000003606
|View full text |Cite
|
Sign up to set email alerts
|

Beyond pain and disability: The lasting effects of trauma on life after injury

Abstract: In support of improving patient care, this activity has been planned and implemented by CineMed and the American Association for the Surgery of Trauma. CineMed is jointly accredited by the Accreditation Council for Continuing Medical Education (ACCME), the Accreditation Council for Pharmacy Education (ACPE), and the American Nurses Credentialing Center (ANCC), to provide continuing education for the healthcare team. AMA PRA Category 1 Credits™CineMed designates this enduing material for a maximum of 1 AMA PRA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…This would be consistent with a body of literature showing that an individual’s global traumatic stress burden over time is a predictor for PTSD development 28,29 . This study is one of many affirming the need for a robust posttrauma support network to address the impacts of injury on medical comorbidity, substance abuse, mental health, physical function, and societal participation 5–9,30 …”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This would be consistent with a body of literature showing that an individual’s global traumatic stress burden over time is a predictor for PTSD development 28,29 . This study is one of many affirming the need for a robust posttrauma support network to address the impacts of injury on medical comorbidity, substance abuse, mental health, physical function, and societal participation 5–9,30 …”
Section: Discussionsupporting
confidence: 87%
“…A higher proportion of patients with PTI screened positive for PTSD at 6-month follow-up, although this difference was not statistically significant (14 [37.8%] vs. 11 [20.0%], p = 0.059). Pain intensity scores were similar between patients with and without PTI at 6 months (5 [1][2][3][4][5][6][7] vs. 3 [1][2][3][4][5][6][7], p = 0.92). There were no significant differences in the change of T score over 6 months of follow-up in most health domains between patients with and without PTI (Table 5).…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…But shouldn't we? A study by Hatchimonji et al 7 was presented at EAST last year showed the lingering effect of trauma, not just on depression, but on other facets of life that patient’s value such as the ability to participate in social activities.…”
mentioning
confidence: 99%